Group B Streptococcal Renal Abscess in a 17-Year-Old Girl with Type 1 Diabetes Mellitus - Kyeong Eun Oh; Hyung Eun Yim; Kee Hwan Yoo (Korean Society of Pediatric Nephrology, 2020)
Streptococcus agalactiae or group B streptococcus (GBS) is associated with infections in neonates and pregnant women. Herein, we describe a rare case of GBS renal abscess with peritonitis and pleural effusion in a 17-year-old girl with type 1 diabetes mellitus. The girl was admitted due to fever and right flank pain. Laboratory findings included leukocytosis and increased C-reactive protein level and erythrocyte sedimentation rate. Her serum glucose level was 484 mg/dL. Urinalysis showed no pyuria. Renal sonography revealed parenchymal swelling in the right kidney. The patient was administered intravenous cefotaxime. Urine and blood cultures were negative. Fever seemed to improve, but the following day, she complained of abdominal pain and fever. Antibiotic was switched to imipenem, and abdominal and pelvic CT revealed a ruptured right renal abscess, peritonitis, and bilateral pleural effusion with atelectasis. Pigtail catheter drainage of the abscess was performed. Culture from the abscess was positive for GBS, and fever subsided 2 days after the drainage. She was discharged with oral cefixime. The clinical course of urinary tract infections (UTIs) can be atypical in patients with diabetes, and GBS can be a cause of UTIs. Prompt diagnosis and management are necessary to prevent complications in patients showing atypical courses.